Digital Entrepreneurship Strategy and Suburban Food Waste Mitigation Application Prototype - Luthfiyah Sakinah; Adam Mukharil Bachtiar; Nafisa Burikulovna Gulyamova (Universitas Komputer Indonesia, 2026)
The result is that suburban culinary SMEs are confronted with the dilemma of food waste, a daily spoilage of food that they often have to bear the brunt of financial loss because of it. In this paper, we propose a digital entrepreneurship business model and a location-based application prototype for food waste reduction, using the Business Model Canvas (BMC) model and the Haversine Algorithm. Based on the Design Science Research (DSR) approach, the study includes problem identification through partner interviews, quantitative consumer surveys, and IT artifact design. Validation of the business model suggests the 15% commission scheme on the 50–70% discounted products will be perceived as a reasonable and fair loss mitigation strategy by the majority of the business owners, although facing operational friction with one partner dissent. The BMC analysis aligns the value proposition of the platform to meet the needs of balancing the consumer’s economic motives and the efficiency needs of the partner. Technologically speaking, the system uses Location-Based Service (LBS) to automatically suggest the nearest partners in real-time. Simulation test with the Haversine formula verified highly reliable output with an average deviation of 0.11 km or an error percentage of 2.05% compared with the Google Maps data, yielding a practical localized computational accuracy of 97.95%. This study strengthens the contribution to an inclusive digital ecosystem in satellite regions by way of a feasible PWA approach that furthers global SDG at mitigating food waste